Sulbactam–Durlobactam: A Novel Antibiotic Combination for the Treatment of Acinetobacter baumannii–Calcoaceticus Complex (ABC) Hospital-Acquired Bacterial Pneumonia and Ventilator-Associated Bacterial Pneumonia - Wissam K. Kabbara; Elina Sadek; Hanine Mansour (Canadian Journal of Infectious Diseases and Medical Microbiology)
Summary: Sulbactam–durlobactam is a recently approved antimicrobial combination of two β-lactamase inhibitors for the treatment of hospital-acquired bacterial pneumonia (HABP) and ventilator-associated bacterial pneumonia (VABP) associated with Acinetobacter baumannii–calcoaceticus complex (ABC) in patients 18 years and older. Sulbactam is a direct antibacterial activity with high susceptibility to A. baumannii species. Durlobactam, diazabicyclooctane β-lactamase inhibitors possesses a broad-spectrum activity against Ambler class A, C, and D serine β-lactamases. This combination has been studied to overcome resistance to ABC species. Data were obtained from in vitro and preclinical studies as well as phase I, II, and III clinical studies published in English between 200t0 and January 2023. A phase II trial showed similar tolerability and pharmacokinetics parameters of sulbactam–durlobactam in patients with urinary tract infections to placebo. However, no ABC infections were included in the trial. ATTACK, a phase III clinical trial of sulbactam–durlobactam, studied the safety and efficacy of sulbactam–durlobactam in patients with ABC HABP/VABP and showed its noninferiority to colistin. Reported adverse events include anemia, elevated liver enzymes, hyperkalemia, headache, diarrhea, nausea, urticaria, and vascular pain. Sulbactam–durlobactam is a new β-lactamase inhibitors combination active against MDR Gram-negative bacteria including ABC. It is currently approved for the treatment of HABP/VABP caused by susceptible ABC strains.